Peningkatan Kompetensi Guru Pengajar TPQ Al-Furqon Betokan Krajan Demak Melalui Pelatihan Softskills Public Speaking dan Team Work - Dian Prawitasari; Sih Darmi Astuti; Ana Kadarningsih (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
The problem that occurs at TPQ Al Furqon is the lack of teacher competence, especially soft skills. So the teachers at TPQ Al-Furqon Demak need soft skills training to improve their teaching and learning competence. This soft skills training takes the form of public speaking and team work with the aim of learning the Koran to run effectively and efficiently. Apart from that, this training aims to create an atmosphere of Teaching and Learning Activities (KBM) that is structured, clear and directed according to their respective roles. The approach method used includes the FGD (Focus Group Discussion) approach including sharing sessions. The activity stages consist of the counseling or material delivery stage, the training practice stage and the training evaluation stage including sharing sessions. This activities result show that teachers understand the importance of public speaking and team work so that teaching and learning activities more interesting and effective.